Analysis of the Prolonged Maintenance and the Accompanying Widespread Precipitation of Typhoon Chaba （2203） Remnant after Landfall - Longsheng LIU; Yinglong XU (Gaoyuan qixiang)
We conducted a comprehensive analysis on the causes of prolonged maintenance and widespread precipitation after the landfall of Typhoon Chaba， using the best track data from the Shanghai Typhoon Research Institute of the China Meteorological Administration， the FNL 0.25°×0.25° reanalysis data and the NOAA 0.5°×0.5° global daily precipitation data.The results show that the main moisture source of the remnant of Chaba in the first phase （3-4 July） was the southerly low-level jet， and the second phase （5-6 July） it was mainly the combination of the southerly low-level jet and the boundary layer easterly jet， which resulted in a rare entire atmosphere precipitable water of 75 mm.The vertical wind shear and water vapor convergence formed by the coupling of the double low-level jets provided favorable dynamic conditions for the occurrence and maintenance of heavy rainfall.A cold pool was formed near the surface to the west of the vortex with the intrusion of cold air， which caused the Chaba remnant to gradually degenerate into an extratropical cyclone with a significant increase in baroclinic kinetic energy.In the view of potential divergence diagnosis， we found that as the Chaba remnant kept moving northward to approach the subtropical westerly jet， the vertical wind shear at high and low levels increased.The cold air carried by the high-altitude cold vortex turns the Chaba residual vortex to baroclinic system.The easterly wind jet in the boundary layer increased the instability of the layer below 850 hPa， which provided unstable energy conditions for the occurrence and maintenance of heavy rainfall.